Pengaruh ROA, ROE, Dan DER Terhadap Nilai Perusahaan Pada Perusahaan Jasa Properti - Hutabarat, William Loro Sae; Fazhar Sumantri; Theysa Sahlani Pratiwi (JRAK (Jurnal Riset Akuntansi dan Bisnis), 2025)
The property sector in Indonesia, including companies like PT Adhi Commuter Properti, Tbk, is highly sensitive to fiscal policies, interest rate fluctuations, and market conditions. Over the years 2005 to 2023, the company experienced inconsistent fluctuations in Earning Per Share (EPS) that were not always aligned with changes in its financial ratios, particularly Return on Assets (ROA), Return on Equity (ROE), and Debt to Equity Ratio (DER). This raised concerns about whether these financial indicators reliably reflect the firm’s value. The purpose of this study is to examine how Return on Equity (ROE), Return on Assets (ROA), and Debt to Equity Ratio (DER) affect EPS, which is a measure of business value at PT Adhi Commuter Properti, Tbk. The study uses a causal associative design and a quantitative methodology. Annual financial reports serve as the source of secondary data. Descriptive statistics, multiple linear regression, the partial (t) test, the simultaneous (F) test, the coefficient of determination (R2), and the classical assumption tests (normality, multicollinearity, heteroscedasticity, and autocorrelation) are among the analytical methods used. The findings indicate that while ROA, ROE, and DER do not significantly affect EPS on their own, they do significantly affect EPS when combined. The 54.5% coefficient of determination value shows that the independent variables may account for EPS, with the remaining portion being impacted by extraneous variables.